Feminism Reflected in 7 Hati 7 Cinta 7 Wanita By Robby Ertanto Soediskam: A Literary Feminist Analysis - Andi Ilham Ilyas; Jean Pauline Trilles- Pocaan; Kuliga Tanasavate (Journal of Language, Literature, and Educational Research, 2025)
Purpose of the study: This study aims to describe the representation of feminism in the film 7 Hati 7 Cinta 7 Wanita directed by Robby Ertanto Soediskam through a literary feminist lens. Methodology: This study used a descriptive qualitative method. The main data were collected from the film 7 Hati 7 Cinta 7 Wanita by Robby Ertanto Soediskam, analyzed using feminist literary criticism. Main Findings: The film portrays various forms of women’s struggles against patriarchal domination. Each female character reflects a unique aspect of feminist resistance, with Dr. Kartini as the central figure who advocates for women’s rights. Novelty/Originality of this study: This study offers a feminist interpretation of a contemporary Indonesian film that has not been extensively explored in academic research. It highlights how visual narratives serve as a platform for feminist messages in modern literature and cinema.